Fiscal Policy and Economic Performance: A Review - Halkos, George E.; A. Paizanos, Epameinondas (Journal of Reviews on Global Economics, 2016)
The economic implications of government expenditure have been shown to be significant and broad. In particular, government spending has been shown to enhance long-run economic growth by increasing the level of human capital and Research and Development (R&D) expenditure, and by improving public infrastructure. On the other hand, there is evidence that a greater size of government spending may be less efficient and therefore not necessarily associated with a better provision of public goods and higher levels of economic growth. Moreover, it is likely that the size of government expenditure and its composition are associated with key aspects of the quality of growth, such as income inequality and environmental sustainability. This paper presents a review of the theoretical and empirical literature on the relationship between fiscal policy and economic activity, both in terms of long-run economic growth and short-term output fluctuations. In general, empirical evidence on these relationships is not robust and remains inconclusive.